Organizational Theories Within the Context of Human Resource Marketing - Minder, Susanna (European Scientific Journal, ESJ, 2019)
Human Resource Marketing with all its sub-processes, sub-fields and research areas is subject to constant development and change. External circumstances like unemployment, lack of qualified and trained employees etc. force organizations to constantly rethink their approach to human Resource Marketing processes like e.g. recruiting. Organizational theories may hereby support the understanding of these complex and sometimes abstract procedures as they give guidance how to cope with this issue. The paper displays recent approaches to connect Human Resource Marketing and Organizational Theories in a way that can be used in different contexts. Hereby organizational Theories are one possibility to explain the need of change for Human Resource Marketing and its processes. The discussions about the different models of change and the variety of views of management and organization fortify - at the end of the paper - the difficult task to decide for only one model. It must be clear that Human Resource Marketing should be treated as a multidimensional concept. Nevertheless, Organizational Theories can be recommended as one approach to measure a company´s organizational performance. Human Resource Marketing´s integration into Organization Theory is not an easy to fulfill task and leaves way to further considerations in the area of Human Resource Management and its Marketing approach.